STUDY OF MAGNETIC SUSCEPTIBILITY IN THE EXPLORATION OF CRITICAL METALS CASE STUDY: LATERITIC SOILS OF SOUTHEAST SULAWESI - Ibrahim, Khalil
Lateritic soils are a prospective source of critical metals that include rare earth elements. In this study, laterite outcrops from Ni-producing areas in Southeast Sulawesi, Indonesia. The aims of this study were (1) to explain the magnetic properties and color characteristics as markers to explain the process of pedogenesis in the soil then in the tropics, (2) to explain the relationship between laterite color and magnetic mineral content, and (3) to determine the relationship between magnetic parameters and the differentiation patterns of critical metals that changed during pedogenesis. The methods in this study include frequency-based magnetic susceptibility measurements, color classification according to the Munsell Soil Color Charts, and geochemical analysis with µ-X Ray Fluorescence (XRF). From the research results, the increase in magnetic susceptibility is due to the abundance of iron oxide magnetic minerals from the pedogenesis process. The color classification shows that laterite deposits are dominated by hue groups of 5YR – 10 YR which is in line with the increase in magnetic susceptibility. The increase in ?LF and higher ?FD % values indicated that the concentration of SP particles increased with weathering and pedogenesis. Superparamagnetic minerals (SP) turn into other iron oxide minerals such as hematite and goethite due to the leaching process, then the labile minerals mobilize to the lower layers. During the pedogenesis process, there are three distinct patterns from the bottom layer up. The first pattern is enrichment experienced by Sc, La, Cr, and Ti. The second pattern is the depletion experienced by Ni, Nd, and Ho. The third pattern is the localization of high concentration at a certain depth, as experienced by Co, Ce, and Va. The concentration of certain critical metals correlates either positively or negatively with magnetic susceptibility, inferring that magnetic susceptibility might be used as a proxy indicator for exploration critical metal concentration in lateritic soil.